PENGARUH KOMITMEN DAN PROFESIONALISME TERHADAP KINERJA KARYAWAN PADA YAYASAN PONDOK PESANTREN SYEKH MUHAMMAD DAHLAN AEK HAYUARA SIBUHUAN - Husin Ahmadi Hasibuan (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study uses an associative approach methods by using two or more variables to determine the relationship or influence of each other. The research objective to be achieved by the authors of this study is to determine whether the Commitment partially influences Employee Performance at the Sheikh Muhammad Dahlan Aek Hayuara Sibuhuan Islamic Boarding School Foundation, does Professionalism partially affect Employee Performance at the Sheik Muhammad Dahlan Aek Hayuara Sibuhuan Islamic Boarding School Foundation, and whether Commitment and Professionalism have a simultaneous influence on employee performance at the Sheikh Muhammad Dahlan Aek Hayuara Sibuhuan Islamic Boarding School Foundation. The data collection technique in this study is by distributing questionnaires that have been prepared and given to the respondents. The population in this study were all teacher employees in the foundation which amounted to 64 people, with the sampling used being equal to 64 people. The data analysis techniques used are Technical data analysis, Multiple Linear Regression Analysis Test, Classical Assumption Test and Hypothesis Test namely t Test (Partial), Test f (Simultaneous) and Coefficient of Determination (R2).